Antinociceptive evaluation of Buddleja davidii Franch flower extracts and the involvement of martynoside - Mark English; Mariana Martins Gomes Pinheiro; Thais Biondino Sardella; Patricia Dias Fernandes; Karastika Rahayu Abdul-Wahab; Liam O’Sullivan; Fabio Boylan
Buddleja davidii Franch (Buddlejaceae) is traditionally and historically used for injury healing and for its anti-inflammatory and anti-bacterial effects. In the present study the antinociceptive effects of crude ethanol extract (CEE), ethyl acetate (EA) and butanol (B) fractions obtained from the flowers were investigated, together with martynoside, using different nociception models (formalin- and capsaicin-induced licking response and hot plate). Mice were treated with CEE, EA and B (10, 30, 100 mg/kg, p.o.), martynoside (2.5, 5 and 7.5 mg/kg, p.o.), acetylsalicylic acid (ASA, 100 mg/kg, p.o.) and morphine (5 mg/kg, s.c.). CEE and its fractions inhibited response in the second phase of the formalin model. The EA and B fractions also exhibited inhibition in the first phase of the formalin model. Martynoside inhibited both phases. To elucidate the antinociceptive mechanism of action of CEE, EA, B and martynoside the animals were pre-treated by subcutaneous administration of naloxone (1 mg/kg), atropine (1 mg/kg), mecamylamine (2 mg/kg), yohimbine (2 mg/kg), L-nitro arginine methyl ester (L-NAME, 3 mg/kg) or glibenclamide (2 mg/kg). The antinociceptive effect of CEE, EA, B and martynoside was inhibited by atropine. Naloxone inhibited the antinociceptive effect of CEE, B and martynoside. L-NAME reduced the antinociception of CEE and martynoside. Mecamylamine inhibited the effect of B and martynoside. Administration of yohimbine had no effect. Crude ethanol extract of Buddleja davidii flowers and its fractions exhibit antinociceptive activity, which is at least in part due to the presence of martynoside. Evaluation of their mechanism of action indicated a significant influence of the cholinergic system and to a lesser extent of other pathways such as L-arginine, nitric oxide, ATP-sensitive potassium channel and opioid pathways